Assessment of Brix values for estimating nitrogen and gross energy concentrations of pig urine: a technical note - Jeonghyeon Son; Hyunseok Do; Beob Gyun Kim (Animal Bioscience)
The present study aimed to develop equations for estimating the dry matter (DM), nitrogen (N), and gross energy (GE) concentrations in pig urine using Brix values. A total of 96 urine samples were obtained from pigs of 6.0 to 62.2 kg initial body weight fed 12 diets in three experiments. The animals were fed a corn-soybean meal-based diet or a corn diet. The N concentrations in the urine samples ranged from 0.12% to 2.06% and the GE concentrations ranged from 2 to 187 kcal/kg. The urine Brix values were positively correlated with urinary DM, N, and GE concentrations (r = 0.94, 0.87, and 0.93, respectively; p<0.001). The models for estimating urinary DM, N, and GE concentrations were: urinary DM (%) = 0.590×Brix+0.315 (r2 = 0.91; p<0.001); urinary N (%) = 0.0798×Brix+ 0.148 (r2 = 0.84; p<0.001); urinary GE (kcal/kg) = 11.96×Brix+2.33 (r2 = 0.87; p<0.001), where the Brix value of urine is expressed as %. Overall, the Brix values correlated positively with the DM, N, and GE concentrations in pig urine and can thus be used for estimating the concentrations of these urinary components.